Laboratory Examination in Congenital Adrenal Hyperplasia: A Literature Review - Raja Iqbal Mulya Harahap; Tiene Rostini; Nida Suraya; Srawana Ayu Renaningtyas (Journal of World Science, 2026)
Congenital adrenal hyperplasia (CAH) is a group of inherited genetic disorders that affect the adrenal glands, which produce essential hormones such as cortisol, aldosterone, and sex steroids. The most common form of CAH is caused by a 21-hydroxylase enzyme deficiency resulting from mutations in the CYP21A2 gene. This deficiency disrupts normal cortisol and aldosterone production, leading to excessive androgen synthesis and a range of clinical manifestations, including ambiguous genitalia in females and adrenal crisis in both sexes. Current biomarkers, such as 17-hydroxyprogesterone (17-OHP), androstenedione, and testosterone, have limitations, and further research on 11-oxygenated androgens—which are more specific for CAH—is needed. Non-invasive methods, such as measuring steroids in saliva and urine, are increasingly accessible and useful, particularly for children showing signs of hyperandrogenism.